2022
DOI: 10.3389/fendo.2022.859245
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Trends of Pediatric Obesity and BMI z-Score From 2017-2021 in China: Comparable Findings From Real-World Mobile- and Hospital-Based Data

Abstract: IntroductionLifestyle changes including COVID-19 lockdown cause weight gain and may change obesity trends; however, timely changes are largely unknown and monitoring measures are usually lack. This first large-scale study aimed to analyze the real-world national trends of obesity prevalence of Chinese children in the past five years, and the impact of COVID-19 pandemic on pediatric obesity development through both mobile- and hospital-based data.MethodsThis study included children aged 3 to 19 years old all ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
7
1
2
Order By: Relevance
“…The overweight and obesity rates of AH children are higher than those of Chinese children reported by the recent nationwide research 13 (control group) ( p <0.05). For AH girls, there is no significant difference in overweight and obesity rates compared with the reported prevalence.…”
Section: Resultscontrasting
confidence: 52%
See 3 more Smart Citations
“…The overweight and obesity rates of AH children are higher than those of Chinese children reported by the recent nationwide research 13 (control group) ( p <0.05). For AH girls, there is no significant difference in overweight and obesity rates compared with the reported prevalence.…”
Section: Resultscontrasting
confidence: 52%
“…And we compared the growing development data of AH patients with the national survey of children. 13 The overweight and obesity rate of AH children was significantly higher than in the control group. 13 This is consistent with the previous studies that have suggested a possible association between obesity and adenotonsillar hypertrophy.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The study seized kindergarten closure as an opportunity to observe the impact of lifestyle changes on the OWO rates in Chinese preschool-age children. Although there have been some studies, including Chinese studies, investigating the relationships between the COVID-19 pandemic and physical activity, screen time, and diets [ 35 , 56 ], few studies have examined the impact of kindergarten or school closures on the prevalence of OWO using large and high-quality school-based anthropometric data and have performed four years of repeated data analysis. The limitation of the study was that private kindergartens were not included, which might lead to selection bias.…”
Section: Discussionmentioning
confidence: 99%